The EU and global public goods: Challenges and opportunities - Mikaela Gavas (Danish Institute for International Studies (DIIS), 2013)
Over the last decade, development cooperation has evolved to such an extent that we are now entering 'a new age of global development', characterised by an emphasis on global public goods (GPGs). The increasingly global nature of development challenges clearly indicates that global problems require global solutions and new forms of international cooperation with the involvement of emerging and developing countries. The EU has the potential to play a leading role in the provision of GPGs. Although the EU has played a key role in the provision of GPGs, notably on climate policy and food security, it lacks a common strategy for addressing GPG challenges. The EU needs to adapt to the changing global landscape, improve its internal coherence and promote a global vision and development approach with common narratives on the challenges that need to be tackled. In order to realise its potential, the EU should: be selective about the issues that it can realistically tackle; develop clear strategies, commit the necessary resources to implement the strategies, improve its internal coordination and policy coherence, agree a 'division of labour' between the EU institutions and the Member States, and focus on strategic partnerships and invest in alliances with countries that promote multilateral solutions.
Keywords: 300